Menstrual management among adolescent girls in Uttar Pradesh, India: An examination of interpersonal and mediated communication as delivery mechanisms for practical guidance - Block, Suzanne J.; Hauer, Michael K.; Ezeh, Alex; Sood, Suruchi (Frontiers in Reproductive Health, 2023)
Background: Adolescent girls' right to achieve menstrual health and hygiene management (MHHM) healthfully is yet to be realized. One reason is the lack of practical guidance on the procurement, use, and disposal of menstrual products. This study defined interpersonal practical guidance (IPG) as face-to-face communication and mediated practical guidance (MPG) as social and behavior change communication (SBCC) intervention-driven communications through print and media materials. We examine the impact of these two delivery mechanisms of practical guidance on adolescent MHHM knowledge, attitudes, and practices (KAP) following an SBCC intervention in India. Objectives: To understand how IPG and SBCC-driven MPG independently influence adolescent girls’ KAP on the procurement, use, and disposal of menstrual products and whether those who receive both IPG and MPG have better KAP related to the procurement, use, and disposal of menstrual cloth or sanitary pads than those who receive only one form of practical guidance or none at all. Methods: Adolescent girls' questionnaire responses from GARIMA's case-comparison evaluation were analyzed using Stata/SE 17 (n= 2,384). Girls were matched on sociodemographic and socioeconomic variables. Chi-square analysis examined relationships between sociodemographic, practical guidance, and KAP variables. Multivariate logistic regression assessed associations between practical guidance and KAP variables. Results: There are significant associations between adolescent girls’ KAP depending on whether they received IPG, SBCC-driven MPG, or both. IPG and MPG delivered together has greater odds of predicting correct menstrual management KAP than when delivered separately. These effects were most notable for adolescent girls’ knowledge and practices related to using and disposing of menstrual hygiene products. Conclusion: There is urgent need to create positive, sustainable changes to address menstrual health and hygiene management. This study introduces an innovative approach that utilizes interpersonal and mediated communication as mechanisms to deliver practical guidance on menstrual management. Future interventions should implement and evaluate to better understand the role of practical guidance in ensuring all women and girls are prepared to confidently manage their menstrual health.